Determination of the enantiomeric composition of amphetamine, methamphetamine and 3,4-methylendioxy-N-methylamphetamine in seized street drug samples from southern Germany - Losacker, Moritz; Zörntlein, Siegfried; Schwarze, Bernd; Staudt, Svenja; Röhrich, Jörg; Hess, Cornelius (Drug Testing and Analysis, 2021)
Amphetamine (speed), methamphetamine (crystal meth), and 3,4-methylenedioxy-N-methylamphetamine (MDMA, ecstasy) represent the most frequently abused amphetamine-type stimulants (ATS). Differences in pharmacological potency and metabolism have been shown for the enantiomers of all three stimulants. Legal consequences in cases of drug possession may also differ according to the German law depending on the enantiomeric composition of the seized drug. Therefore, enantioselective monitoring of seized specimens is crucial for legal and forensic casework. Various kinds of samples of amphetamine (n = 143), MDMA (n = 94), and methamphetamine (n = 528) that were seized in southern Germany in 2019 and 2020 were analyzed for their chiral composition using different chromatographic methods. Whereas all samples of amphetamine and MDMA were racemic mixtures, the chiral composition of the methamphetamine specimens was diverse. Although the vast majority (n = 502) was present as (S)-methamphetamine, also specimens containing pure (R)-methamphetamine (n = 7) were found. Furthermore, few samples (n = 8) were of racemic nature or contained non-racemic mixtures of both enantiomers (n = 10). Because methamphetamine appears in varying enantiomeric compositions, any seizure should be analyzed using an enantioselective method. Amphetamine and MDMA, on the other hand, currently appear to be synthesized exclusively via racemic pathways and are not chirally purified. Nevertheless, regular monitoring of the chiral composition should be ensured.
CRIS-Team Scopus Importer:2021-07-16
Keywords: amphetamines; chiral chromatography; enantiomers; forensic toxicology; seizures

Lithiumnachweis bei exhumierten Leichen: Vergleichende Untersuchungen von Knochensubstanz und Erdreich bei V. a. todesursächliche Lithiumintoxikation - Stöver, A.; Roider, G.; Schwarze, Bernd; Staudt, Svenja; Graw, M.; Schöpfer, J. (Rechtsmedizin, 2019)
Background: Lithium salts have been used in psychiatric therapy for decades. The endogenous lithium content of organs and body fluids is just as heterogeneous as the content due to medication. There are no comparative data in the literature on endogenous or medication-related lithium contents and distribution in a corpse in cases of advanced putrefaction. Data on the possible transfer of lithium from or into surrounding soil also do not exist. In view of the lack of sufficient data in the literature on post-mortem lithium concentrations in bone with or without lithium medication, it seemed reasonable to carry out investigations. Material and method: The study included samples from a total of five adult corpses plus soil samples from the area where the bodies were found. After exact weighing and appropriate sample preparation with a graphite furnace AAS (graphite furnace atomic absorption spectroscopy, spectrometer ZEEnit650 graphite furnace, Analytik Jena) the sample material (bone, bone marrow, soil) was measured against an aqueous calibration by the method of standard addition and, if necessary in lower concentration ranges. Results: The lithium concentrations detected in the skeletal samples from cases I, II and III (no references about lithium therapy) were 70–130 μg/kg wet weight for bone and 10–20 μg/kg wet weight for bone marrow. They differed by a factor of ca. 200 compared to the concentration in lithium-based medication for bones and by a factor of ca. 400 for bone marrow. Furthermore, it was shown that all bone marrow concentrations were significantly lower compared to the concentrations in bone. The measured lithium content of all soil samples examined in the collective was 10–30 mg/kg of soil and in a comparatively middle range worldwide. Conclusion: Because of the lack of comparative values in the literature, lithium concentrations in bone, bone marrow and soil samples of exhumed or buried corpses were examined and compared to results in corpses with lithium therapy before death. The lithium concentrations found in the bone substance of lithium-medicated and non-medicated corpses showed highly statistically significant differences of 2–4 × 102. A measurement of the lithium concentrations in corpses in a state of advanced putrefaction or skeletonized corpses, in bone marrow and/or only bone seems to be a useful to identify cases of lithium medication or poisoning; however, based on current data a distinction between therapeutic use and poisoning is not yet sufficiently possible.
CRIS-Team Scopus Importer:2019-11-01
Keywords: Atomic absorption spectroscopy; Bone; Exhumation; Lithium; Poisoning